Academic achievement among university students: The role of causal attribution of academic success and failure - Asina Christina Rosito (HUMANITAS: Indonesian Psychological Journal, 2020)
Previous studies have attempted to understand various motivational factors that affect academic achievement. One of the cognitive factors this study focuses on is the causal attribution of academic success and failure. Causal attribution refers to one's perception of the factors that cause learning success and failure. These perceptions encompass three dimensions: locus of causality, stability, and personal control. This study aimed to determine whether causal attribution of academic success and failure predicts academic achievement. 156 students of Universitas HKBP Nommensen across batch years and majors participated in this study. An adapted version of the Causal Dimension Scale was employed as the research instrument. Academic performance was measured using the Grade Point Average (GPA). The simple linear regression analysis results highlight that causal attribution is a significant predictor of academic achievement. Differences in causal attribution between high performing and low performing students were identified. The results imply that personal control is the significant dimension of predicting student's performance, which means that student's beliefs about their capacity to control causal factors, will become a good predictor of their performance. Therefore the more higher students' believe that they are able to control causal factors will enhacnce their academic achievement.